Leaf gas exchange recovery of soybean from water-deficit stress. Issue 6 (1st November 2020) - Rosas-Anderson, Pablo; Sinclair, Thomas R.; Locke, Anna; Carter, Thomas E.; Rufty, Thomas W.
ABSTRACT: As the risk of drought attributable to climate change increases, the development of high-yielding, drought-adapted cultivars will be critical for minimizing yield losses in crops like soybean ( Glycine max (L.) Merr.). In this study, the ability of soybean genotypes to recover transpiration and leaf gas exchange capacity following re-watering from soil drying was investigated. The plants were subjected to controlled water-deficit stress and recovery in growth-chamber experiments. Transpiration was measured on five soybean genotypes and photosynthesis rates on two select genotypes. After water re-supply, transpiration was initially low but increased until a stable rate was reached on day 3, to about 50% to 100% of the rates of reference plants that had not been stressed. The largest difference in maximum transpiration recovery was between the varieties USDA-N8002 and Benning compared to the landrace Geden Shirazu, with Geden Shirazu having the lowest recovery. Photosynthesis and vapor-pressure-deficit response measurements did not show that restricted plant stomatal conductance was responsible for the limitation observed in Geden Shirazu recovery. Since all genotypes showed rapid recovery from water-deficit stress in 3 d, more rapid recovery was not indicated as a major candidate for improving soybean drought tolerance. However, the extent of recovery varied among genotypes and those genotypes that fully recovered to rates of well-watered plants such as Benning and USDA-N8002 would seemingly be advantageous for drought conditions.